Simplification of Punjabi Sentences: Converting Complex Participial Sentences into Simple Sentences - Jindal, R. M.; Rana, V.; Sharma, S. K. (EAI Endorsed Transactions on Scalable Information Systems, 2020)
INTRODUCTION: In this world of internet and artificial intelligence, Natural Language Processing has emerged as most demanding research area. Under Natural Language Processing, sentence simplification is one of the research area that deals with simplification or conversion of complex sentences in to simple sentences.OBJECTIVES: In this research article, author has proposed a novel approach for conversion (simplification) of complex sentences (participial type) of Punjabi language into easily understandable simple sentences.METHODS: Author performed lexical and morphological simplification by using morphological features of the language. Morphological features are used to identify the participial type complex sentences.RESULTS: on testing the proposed algorithm, a precision of 96.39%, recall of 91.37% and Fmeasure as 93.79% was reported.CONCLUSION: the developed system can be helpful for Aphasic and Dyslexia readers and can be used as subpart for machine translation system, summarization system and other Natural Language Processing applications.
Keywords: Paraphrasing; sentence simplification; participial sentences; Punjabi language; complex sentences